Evaluation of morphological traits, phytochemical compositions and antioxidant properties of watercress leaves - Sakil, MA; Polash, MAS; Afrin, S; Hossain, MA (Progressive Agriculture, 2019)
Despite the significant nutritional and health values, watercress (Nasturtium officinale L.) is still insufficiently known and explored leafy vegetables. Being a native crop of Central Asia ensure possibility of watercress to grow under Bangladesh climate.An experiment was conducted during October 2015 with the aim to evaluate the morphological traits, morphological traits, phytochemical compositions and antioxidant properties of the leaves of watercress. The experiment was designed with Completely RandomizedDesign (CRD) with three replications. The results showed, average watercress shoot biomass was 38.60 ± 3.41 g plant-1. In case of leaf pigment composition the chlorophyll a and b was 70.45 ± 11.97 and28.32 ± 4.37 mg 100 g-1 FW. On an average, the increasing order of the nutrients of proximate analysis in fresh sample was fat<ash<carbohydrate<protein<moisture. Besides those, mineral composition and antioxidant properties of watercress leaves were evaluated. Potassium mineral concentration was highest in watercress leaves 278±45% w.b. followed by Calcium 131±13 % w.b. The ascorbic acid was found in highest concentration 70.57±5.78 mg/100g fresh weight. Results also showed 50.42±2.77 mg GAE/g phenols and 0.13±0.03 mg/ml DPPH radicle scavenging activity in watercress. Progressive Agriculture, Vol. 30, Suppl. 1: 10-16, 2019